An Observation of Crimp Pattern in a Rat Medial Collateral Ligament - Inoue, Akio; Miyazaki, Michio; Tanaka, Nobuhiro; Yamaki, Kouichi; Soejima, Takashi; Horibe, Shuji (Orthopedics & Traumatology, 1993)
Changes in crimp pattern were observed under video microscope during tensile and stress relaxation tests. Crimp unfolded with increasing stress and vanished at 1.4% strain, but refolded with decreasing stress reappearing at 4.24% strain. No change was found in the relaxation phase. After relaxation crimp pattern was rougher than before. We speculated that stress relaxation makes changes in the microstructure of fiber bundles.